Determinants of medical students' empathy during clinical rotation - Resiana Citra; Rizma Adlia Syakurah; Eddy Roflin (Intelektual Pustaka Media Utama, 2021)
Medical students in clinical rotation level have been developed comprehension and implementation of empathy, considering that they have already dealt with patients in the first hand, whereas professionalism and ethics are two main competences as a physician. This study aims to discuss and investigates determinants of medical students’ empathy towards their patients during clinical rotation in the hospital. A qualitative study with phenomenology approach using focus group discussion (FGD) was accompanied with an open-ended questionnaire to serve as preliminary data and basis of FGD topic guidelines involved fourth and fifth grade medical students that has to pass one and/or two of these stages out of the 15 stages in clinical rotation. As much 191 students participated of the written questionnaire and 28 students agree upon voluntarily joining the FGD, which is held with a snowball sampling approach and finishes in five batches. The three main determinants are: i) Internal factors: knowledge about the importance of empathy, direct experience, personality, motivation, mood (emotion), and personal experience; ii) Patient’s and patient’s family factors: patient’s attitudes, patient’s family’s attitudes, patient’s socioeconomic status, patient's illness type and severity; and iii) Environment factors: burnout, satisfaction or appreciation in the job, work environment, and role models. Many factors influence medical students in expressing and implementing empathy as they are taught to do to their patients. Medical school as an institution responsible for upholding the professionalism and ethical standard can help to create more suitable environment for the students to ensure maximum learning experience.